A short review on RAFT polymerization of less activated monomers. Issue 3 (11th April 2022) - Tilottama, Baisakhi; Manojkumar, Kasina; Haribabu, P. M.; Vijayakrishna, Kari
Abstract: Polymers derived from vinyl acetate, N-vinyl carbazole, N-vinyl pyrrolidone, and N-vinyl imidazole possess very interesting properties hence finding applications in pharmaceutical, cosmetics, textile, painting, paper, electric/electronic industries etc . However, these monomers are considered as less activated monomers (LAMs), which fall under the category of non-stabilized monomers. The higher reactivity as well as instability of the propagating radicals of these LAMs pose a challenge toward their controlled polymerization. Reversible addition-fragmentation chain transfer (RAFT) polymerization facilitated the polymerization of LAMs in a controlled fashion affording polymers with narrow dispersity. This review article deals with the study of different xanthate, dithiocarbonate, trithiocarbonate and dithioester based RAFT agents with varying activating and leaving groups for the polymerization of vinyl acetate, N -vinyl carbazole, N -vinyl pyrrolidone, and N -vinyl imidazole. Graphical Abstract: UF0001